Online communication of European public institutions and NATO during the crisis in Ukraine (February 24, 2022 - December 24, 2022) - Tasențe, Tănase (Technium Social Sciences Journal, 2023)
The crisis in Ukraine between February 24, 2022 and December 24, 2022 drastically altered the way that European public institutions and NATO used Twitter to communicate with the public. In response to the political, economic, and military escalation in Ukraine, European public institutions and NATO used Twitter to disseminate information to the public about their diplomatic efforts in the region, as well as to discuss potential solutions and strategies for de-escalation and long-term resolution of the crisis. Through Twitter, European public institutions and NATO were also able to communicate their concerns about regional stability and the potential implications of the crisis for the entire European continent. Twitter proved to be an invaluable tool for European public institutions and NATO in their efforts to keep the public informed and to potentially influence the political dynamics of the crisis in Ukraine.